Clinical and immunohistochemical features of primary breast cancer and metachronous ovarian and endometrial tumors - Kryzhanivska, A.E.; Dyakiv, I.B.; Kyshakevych, I. (Experimental Oncology, 2018)
The aim of the study was to assess the patterns of development of metachronous cancer (endometrial cancer, EC, and ovarian cancer, OC) in breast cancer (BC) patients dependent of receptor phenotype of breast tumors. Materials and Methods: In the study, 63 patients with ВС, who developed metachronous EC (n = 47) or OC (n = 16) were enrolled. Expression of estrogen receptor (ER), progesterone receptor (PR), HER/2neu was assessed using immunohistochemical approach. Results: BC in patients with metachronous EC and OC was characterized by a different frequency of molecular subtypes with the dominance of luminal A (36%) and B (43%) subtypes. In primary BC, we have established a correlation between ER expression and regional lymph nodes status (r = −0.50, p < 0.05); negative correlation between HER2/neu expression and tumor stage (r = −0.48, p < 0.05); between the molecular subtype of BC and its size (r = −0.33, p <0.05), the molecular subtype of primary BC and metastases in regional lymph nodes (r = 0.27, p <0.05). In the patients with luminal subtype BC metachronous tumors developed with the highest frequency (OC — 50%, EC — 50%). After treatment of primary BC metachronous tumors developed at different period: EC (22.2%) — most often in 3–5 years, OC (11.0%) — after 10 years and more. Conclusion: Our data evidence on the clinical significance of the individual characteristics of the BC, especially its molecular subtype, and the need to calculate the personalized risk of development of metachronous tumors of the reproductive system in patients with the BC. Key Words: breast cancer, metachronous endometrial cancer, metachronous ovarian cancer, hormonal receptors, HER2/neu, immunohistochemistry.